Simultaneous multi-spatial scanning optical coherence tomography (OCT) based on spectrum-slicing of a broadband source. (18th March 2019) - Mekonnen, Taye; Kourmatzis, Agisilaos; Amatoury, Jason; Cheng, Shaokoon
Abstract: This paper reports the characterization of a novel daisy-chained multi-channel optical coherence tomography (MC-OCT) method capable of concurrent scanning at multiple sites along the sample arm length of a low coherence interferometer. For this study, a cascade of two wavelength-based beam splitters is used to split the sample arm beam into three channels, forming three imaging (sensing) units. Channel-specific free-space beam paths are introduced in the sample arm to ensure equal optical path lengths amongst the different sensing beams, and hence, a single reference reflector is employed for simultaneous interrogation of signals reflected from samples (or from different spots of a sample). Realistic simulation is carried out to study the properties of the interference patterns such as axial resolutions and spurious side-lobes. Using a broadband light source of 50 nm bandwidth at 840 nm centre wavelength, the achieved axial resolutions of 24.23 µm, 17.81 µm and 20.49 µm for channels 1, 2 and 3, respectively, are in good correlation with simulations. Experimental results on a 3D-printed phantom further validate the imaging functionality of the system. The findings demonstrate a new single source and single interferometric-based MC-OCT method that can feasibly improve the transverse-scan throughput of conventional OCT.